IDENTIFIKASI KAYU MERANTI PUTIH DAN MERANTI KUNING DENGAN MENGGUNAKAN UJI WARNA (Spot let for identification of white meranti and yellow meranti) - Nenny Sumarliani (Jurnal Penelitian Hasil Hutan, 1993)
White meranti and yellow meranti wood have the same characteristics in texture, color and specific gravity and have the same class in durability and strength, mean while the export tax of white meranti is higher than yellow meranti. To differentiate.between those wood species in the field, it has been done a spot test methode, using 5 % ferric amonium sulphate. the results showed that yellow meranti wood responded positively (indicated black spots), while white meranti responded negatively.